2013
DOI: 10.1007/s00167-013-2640-7
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic autologous chondrocyte implantation in the ankle joint

Abstract: IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 36 publications
5
67
0
3
Order By: Relevance
“…The goal of the finest surgical procedure should be the regeneration, restoring worn tissue with high biomechanical quality hyaline cartilage. To date, only osteochondral grafts and regenerative techniques, like autologous chondrocyte implantation (ACI) and bone marrow-derived cell transplantation (BMDCT), have proven effective at this purpose [4][5][6][7][8][9][10][11][12][13]. Nevertheless, osteochondral autograft is a technically demanding procedure with many drawbacks, and other techniques may be preferable [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of the finest surgical procedure should be the regeneration, restoring worn tissue with high biomechanical quality hyaline cartilage. To date, only osteochondral grafts and regenerative techniques, like autologous chondrocyte implantation (ACI) and bone marrow-derived cell transplantation (BMDCT), have proven effective at this purpose [4][5][6][7][8][9][10][11][12][13]. Nevertheless, osteochondral autograft is a technically demanding procedure with many drawbacks, and other techniques may be preferable [4].…”
Section: Introductionmentioning
confidence: 99%
“…After three to four weeks, they are implanted at the site of the lesion. The technique was firstly performed open-field; then, thanks to the use of scaffolds, an arthroscopic approach was developed, making the procedure easier and faster and reducing the morbidity and costs [5,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, MFx is known to be less effective in patients with larger chondral lesions (2-4 cm 2 ) or early osteoarthritis [13]. In the knee and talus, large chondral defects are successfully treated with autologous chondrocyte implantation (ACI) or matrix-associated autologous chondrocyte implantation (MACI) [14][15][16][17][18][19][20][21][22]. ACI has also been effectively used in the hip.…”
Section: Introductionmentioning
confidence: 99%
“…The mean AOFAS score improved from 36.9 preoperatively to 83.9 postoperatively, and 50% patients returned to previous sports. Giannini et al [44] reported, in what we believe to be the largest case series with the longest follow-up, a study involving 46 ankles with a mean follow-up of 87.2 months. The authors reported that the mean AOFAS score was 92 at final follow-up.…”
Section: Matrix-induced Autologous Chondrocyte Implantationmentioning
confidence: 73%